Targeting cIAP2 in a novel senolytic strategy prevents glioblastoma recurrence after radiotherapy - Nozomi Tomimatsu; Luis Fernando Macedo Di Cristofaro; Suman Kanji; Lorena Samentar; Benjamin Russell Jordan; Ralf Kittler; Amyn A Habib; Jair Machado Espindola-Netto; Tamara Tchkonia; James L Kirkland; Terry C Burns; Jann N Sarkaria; et al. (EMBO Molecular Medicine)
Abstract Glioblastomas (GBM) are routinely treated with high doses of ionizing radiation (IR), yet these tumors recur quickly, and the recurrent tumors are highly therapy resistant. Here, we report that IR-induced senescence of tumor cells counterintuitively spurs GBM recurrence, driven by the senescence-associated secretory phenotype (SASP). We find that irradiated GBM cell lines and patient derived xenograft (PDX) cultures senesce rapidly in a p21-dependent manner. Senescent glioma cells upregulate SASP genes and secrete a panoply of SASP factors, prominently interleukin IL-6, an activator of the JAK-STAT3 pathway. These SASP factors collectively activate the JAK-STAT3 and NF-κB pathways in non-senescent GBM cells, thereby promoting tumor cell proliferation and SASP spreading. Transcriptomic analyses of irradiated GBM cells and the TCGA database reveal that the cellular inhibitor of apoptosis protein 2 (cIAP2), encoded by the BIRC3 gene, is a potential survival factor for senescent glioma cells. Senescent GBM cells not only upregulate BIRC3 but also induce BIRC3 expression and promote radioresistance in non-senescent tumor cells. We find that second mitochondria-derived activator of caspases (SMAC) mimetics targeting cIAP2 act as novel senolytics that trigger apoptosis of senescent GBM cells with minimal toxicity towards normal brain cells. Finally, using both PDX and immunocompetent mouse models of GBM, we show that the SMAC mimetic birinapant, administered as an adjuvant after radiotherapy, can eliminate senescent GBM cells and prevent the emergence of recurrent tumors. Taken together, our results clearly indicate that significant improvement in GBM patient survival may become possible in the clinic by eliminating senescent cells arising after radiotherapy.